Long-Term Efficacy and Safety of a Novel LowDose Triple Single-Pill Combination for the Treatment of Hypertension - Abdul, Salam; H. ASITA, DE SILVA; OJJI, DIKE; Silva, A.P.D.E.; GALAPPATTHY, G.; Lakshman, P.; Kumanan, T.; et, al (Global Heart, 2025)
Background: A novel low-dose triple single-pill combination of antihypertensive drugs (GMRx2) has demonstrated superior blood pressure (BP)-lowering efficacy compared to placebo and dual combinations in short-term randomized double-blind trials. Objectives: To evaluate the long-term BP-lowering efficacy and safety of GMRx2- based treatment when used in normal clinical care. Methods: After completing a four-week double-blind randomised phase, participants from Sri Lanka and Nigeria were enrolled into an open-label extension phase (OLE) with follow-up to one year. The OLE involved treatment and uptitration with GMRx2, of ¼, ½ and standard doses of telmisartan/amlodipine/indapamide (i.e., 10/1.25/0.625 mg, 20/2.5/1.25 mg and 40/5/2.5 mg), and add-on antihypertensive drugs if needed to target a home BP goal of <130/80 mm Hg. Home BP monitoring was continued throughout the follow-up and six follow-up clinic visits were conducted. The primary outcome was percentage of participants with home BP control (<130/80 mmHg) at week 52. Results: From 21 August 2023 to 20 August 2024, 50 participants participated in the OLE, of whom 48 (96%) completed it. The mean age of participants was 49 years and 60% were female. Home and clinic mean BP at enrolment into OLE were 126/79 mmHg and 131/83 mmHg, respectively. At one year, home BP control (<130/80 mmHg) was 60% and clinic BP control (<140/90 mmHg) was 88%. Home mean BP was reduced to 121/78 mmHg after 4 weeks into the OLE and was 120/78 mmHg at one year. For clinic BP, the corresponding values were 126/79 mmHg and 122/77 mmHg. None of the participants discontinued trial treatment due to an adverse event. Conclusions: In a population with mild-to-moderate hypertension, long-term therapy with GMRx2-based treatment achieved high levels of BP control and was well tolerated. Trial registration: NCT04518306.
Keywords: Hypertension; clinical trial; pharmacotherapy; global health; Clinical trial; Pharmacotherapy; Global health